Thoratec CentriMag for Temporary Treatment of Refractory Cardiogenic Shock or Severe Cardiopulmonary Insufficiency: A Systematic Literature Review and Meta-Analysis of Observational Studies - Borisenko, Oleg (Lippincott Williams & Wilkins, 2014)
The aim of the study was to systematically evaluate effect of CentriMag heart pump (Thoratec Corporation) as temporary ventricular assist device (VAD) and part of extracorporeal membrane oxygenation (ECMO) system on outcomes in patients with cardiac or cardiac-respiratory failure. A systematic search was conducted in five databases for the period 2003 to 2012. Fifty-three publications with data for 999 patients, supported with CentriMag, were included. In 72% studies, CentriMag was used as a VAD and in 25% as part of ECMO circuit. Mean duration of VAD support was 25.0 days in precardiotomy group, 10.9 days in postcardiac surgery cardiogenic shock group, 8.8 days in post-transplant graft failure and rejection group, and 16.0 days in post-LVAD placement right ventricular failure group. Survival on support was 82% (95% CI 70–92) for VAD support in precardiotomy cardiogenic shock indication, 63% (95% CI 46–78) in VAD support in postcardiac surgery cardiogenic shock indication, 62% (95% CI 46–76) in VAD support in post-transplant graft rejection or failure indication, and 83% (95% CI 73–92) in VAD support in post-LVAD placement right ventricular failure indication. CentriMag is an effective technology for temporary support of patients with cardiac and cardiorespiratory failure.